The effect of peptide based nutrients on the corrosion of carbon steel in an agar based system. (September 2016) - Spark, Amy; Cole, Ivan; Law, David; Ward, Liam
Highlights: Peptide nutrients have an inhibitive effect on steel corrosion in semi-solid agar. This effect appears to be concentration dependent. Inhibition is due to amine and carboxyl groups on the peptide chains interacting with Fe(II). Abstract: A novel system using semi-solid agar with peptide nutrient additions is being developed as a soil analogue for fundamental corrosion studies involving bacteria. Electrochemical studies revealed these nutrients induced an inhibitive effect on the corrosion of carbon steel, hypothesised to be due to activated side chain groups on the peptides. At more anodic potentials variation in the corrosion current suppression was seen with changing nutrient concentration, suggesting concentration dependence of the inhibition process. Knowledge of the electrochemical effect of this system is essential to fully understand the effect of bacteria on carbon steel in the system in the future.